UPAYA PENINGKATAN HASIL BELAJAR DAN KETERAMPILAN BERPIKIR SISWA MELALUI PENERAPAN PERANGKAT PEMBELAJARAN KONSEP EKOSISTEM LAHAN BASAH DENGAN PENDEKATAN LINGKUNGAN - Sukaji Sukaji; Emmy Sri Mahreda; Bunda Halang; Enny Dwi Pujawati (Universitas Lambung Mangkurat, 2015)
This study aims to: 1) measure whether there is the effect of applying the concept of learning through a wetland ecosystem approach to the environment in SMA 1 Wanaraya on student learning outcomes; 2) measure whether there are differences in the application of the concept of learning the wetland ecosystem approach to learning using the learning environment by not using the environmental approach in SMA 1 Wanaraya on student learning outcomes through the group process: 3) knowing whether there is a relationship between learning outcomes and skills think students learning process through the application of the concept of learning tools wetland ecosystems and the environment approach the learning process does not use environmental approach in SMA 1 Wanaraya. This study uses a variant analysis (ANOVA) on the first purpose. On the second purpose using Arikunto Category Analysis (1998) and Variant Analysis (ANOVA). And the third purpose of analysis used is correlation analysis and correlation criteria using reference analysis Sugiarto (1992). Results of calculations obtained that the adoption of the wetland ecosystem concept learning and the learning environment approach the implementation of research on SMA 1 Wanaraya affect the results of the assessment of student learning, no discernible difference from the value percentage and categories are better and influence the level of keaktifitasan think students who use approach to the environment and there is a weak relationship between learning outcomes but the students' thinking skills.